Effect of Soil Acidity Amelioration on Soil Properties and Yield of French Bean (Phaseolus vulgaris L.) under Rainfed Condition in Arunachal Pradesh - Ampee Tasung; Homeswar Kalita; Bishal Gurung; Shaon Kumar Das; Loitongbam Joymati Chanu; Thejangulie Angami; Badapmain Makdoh; Letngam Touthang; Immanuel Chongboi Hoakip; Thupten Tsomu (International Journal of Economic Plants)
Under rainfed conditions yield potential of French bean reduced in the acid soil of Arunachal Pradesh due to low fertility and metal toxicity. Therefore, the current experiment was conducted in ICAR, Basar, Research Farm during rabi season (October–January) of 2018, 2019 and 2020 to study the effect of soil amelioration using organic amendments combined with inorganic fertilizer on the yield of French bean and important soil properties. The soil amendment treatments i.e., control, vermicompost (Vc), vermicompost+lime (Vc+lime), 50% RDF (Recommended dose of fertilizer), 50% RDF+lime, 50% RDF+Vc, 75% RDF, 75% RDF+lime, 75% RDF+Vc, 100% RDF were laid in randomized block design with three replications. The doses of vermicompost, lime and RDF were 2.5 t ha-1, 400 kg ha-1 and 50-50-50 NPK kg ha-1. Results showed soil pH recorded maximum and exchangeable aluminum, exchangeable acidity and total acidity recorded minimum in 75%RDF+lime. The soil organic carbon, soil cation exchangeable capacity, soil moisture content and soil available nutrients (N, P, K, S, Fe, Mn, Zn, Cu) recorded maximum and soil bulk density recorded minimum in 75%RDF+Vc. Vermicompost along with 75%RDF was most effective in increasing the yield (4.85 t ha-1). The study indicates soil acidity amelioration using vermicompost and/or lime along with inorganic nutrients reduced soil acidity and improved the soil fertility making the soil environment favorable to achieve an optimum yield of French bean in acid soils of Arunachal Pradesh.